P5.010 Prevalence and Predictors of a Positive Cervical Cancer Screening Test in a Sexually Transmitted Infection Clinic in Lilongwe, Malawi. (13th July 2013) - Rosenberg, N E; Kamanga, G; Hoffman, I; Ndalama, B; Mapanje, C; Powers, K; Chiudzu, G; Tang, J; Gopal, S; Hosseinipour, M
Abstract : Background: In Malawi, cervical cancer is the most common cancer among females and a leading cause of cancer-related mortality. Cervical cancer can be averted if pre-cancerous lesions are detected early and treated. Visual Inspection with Acetic Acid (VIA) is an effective screening method for preventing cervical cancer and is sustainable in resource-limited settings. We assessed prevalence and predictors of a positive VIA following its introduction in a sexually transmitted infection (STI) clinic in Lilongwe, Malawi. Methods: From October 2012 to January 2013 all females 25–45 years and females < 25 years at clinician discretion received VIA screening at the Kamuzu Central Hospital STI Clinic. We calculated the prevalence of a positive VIA result and used logistic regression to identify predictors of a positive result. Results: During this 3.5-month period, 86 women had VIA screening results. Median age was 29, 77% were married, 43% had at least some secondary education. Forty three percent were HIV-infected and 63% had an STI using Malawi's syndromic management algorithm. Nineteen percent were VIA-positive, 79% VIA-negative, and 2% VIA-uncertain. The prevalence of a VIA-positive result was 7% in HIV-uninfected women and 33% in HIV-infected women. Factors significantly associated with a positive VIA result were HIV infection (OR: 6.1, 95% CI: 1.5, 24.4) and pain during intercourse (OR: 4.5, 95% CI: 1.2, 16.1). Genital warts (OR: 2.4, 95% CI: 0.5, 10.8) and genital ulcers (OR: 3.1, 95% CI: 0.5, 20.3) were associated with an increased odds of being VIA-positive, though this trend was not statistically significant. Conclusions: The prevalence of an abnormal VIA was high among Malawian women attending an STI clinic, especially for those with HIV. To prevent cervical cancer mortality, further expansion of VIA screening is needed in Malawi for women at high risk.